Community-based death preparation and education: A scoping review. Issue 2 (7th February 2023) - Park, Sungwon; Kim, Hyungkyung; Jang, Min Kyeong; Kim, Hyungsub; Raszewski, Rebecca; Doorenbos, Ardith Z.
Abstract: The COVID-19 pandemic revealed a need for people and communities for death preparation. Few studies have examined community-level interventions for death preparation and education. This scoping review scrutinized the relevant literature following PRISMA 2018 guidelines. Six databases were searched for articles published between 2010 and 2020. We found that cultural, socioeconomic, and individual values affected death preparation and that online courses and life-death education were effective preparation methods. Additional research is needed to identify the population-specific effectiveness of interventions. To fully investigate death preparation and education at the community level, theory-based studies employing quantitative and qualitative methods are also needed.